Latest advances in the study of non-coding RNA-mediated circadian rhythm disorders causing endometrial cancer - Zheng, Ling-tao; Chen, Shao-rong; Zhou, Liang-yu; Huang, Qiao-yi; Chen, Jia-ming; Chen, Wei-hong; Lin, Shu; Shi, Qi-yang (Frontiers in Oncology, 2023)
Endometrial cancer (EC) is one of the most common gynecological cancers, and its risk factors include obesity and metabolic, genetic, and other factors. Recently, the circadian rhythm has also been shown to be associated with EC, as the severity of EC was found to be related to night work and rhythm disorders. Therefore, circadian rhythm disorders (CRDs) may be one of the metabolic diseases underlying EC. Changes in the circadian rhythm are regulated by clock genes (CGs), which in turn are regulated by non-coding RNAs (ncRNAs). More importantly, the mechanism of EC caused by ncRNA-mediated CRDs is gradually being unraveled. Here, we review existing studies and reports and explore the relationship between EC, CRDs, and ncRNAs.